Evaluation of acetylated histones 3 and 4 and histone deacetylases 1, 2 and 6 in cutaneous T-cell lymphoma in dogs - Matiz, Oscar Rodrigo Sierra (2019)
- Cutaneous lymphoma constitutes a form of extranodal lymphoma that affects initially the skin and/or adnexal structures and eventually presents an aggressive clinical behavior, causing internal organ infiltration in late-stage disease. The main immunophenotype is T-cell lymphoma (CTCL) and it represents the most common diagnosed type. It is expected that dogs with CTCL develop resistance to chemotherapy at any point during treatment, resulting in short survival times. A need for new therapeutic targets that improve survival expectation in dogs with CTCL is increasing. In humans, therapies based on epigenetic mechanisms helped to control the disease, since epigenetics became a main objective in the search for longer clinical responses in advance-stages. In the first two reported chapters, CTCL is described with particularities of international literature that contrast with data found in this institution, as well as, the role of epigenetics in the neoplasia carcinogenesis and the mechanism of histone modification as a base for treatment. More specifically, in the second chapter, 21 dogs with CTCL were defined as having high grade CTCL due to their large cell size, absence of epithelial tropism, mean value of Ki67 of 63,9% and estimated survival time of 31 days. Clinicopathological characteristics were analyzed for identifying prognostic markers, being the intrathoracic involvement caused by lymphoma seen on thoracic radiography an independent prognostic factor after multivariate analysis. In the last study, samples of CTCL were evaluated to know the level of acetylated histones (H3Ac and H4Ac) and histone deacetylate enzymes (HDAC) HDAC1, HDAC2 and HDAC6, which were involved in the epigenetic mechanism of histone modification in human CTCL. The objective of this study was to compare samples of CTCL in normal lymphnode, inflammatory cells in skin and normal epithelial cells. All markers (H3Ac, H4Ac, HDAC1, HDAC2 and HDAC6) were found to be higher in CTCL than in normal skin, furthermore, the level of H3Ac was statistically lower in CTCL than in normal lymphnode and an aberrant higher level of H4Ac and HDAC2 was confirmed in CTCL. Additionally, the association of the immunoexpression of H3Ac, H4Ac and HDAC2 classified into two the population, having different survival times (48 days Vs 22 days, p=0.06), suggesting that a histone profile exists in the studied population. This study confirmed that the level of histone deacetylases in CTCL are higher than in normal tissues. Further studies are needed to confirm our results and to support new research in HDAC inhibitors in dogs with CTCL.